Mass Media and Social Dysfunction in Thomas Pynchon’s The Crying of Lot 49: A Socio-Psychoanalytic Reading - Abdulqadr, Kezhan Salar; AL-JUMAILI, Dr. Yasir (Sulaimani Journal for Humanities, 2026)
This paper studies Thomas Pynchon’s The Crying of Lot 49 (1966) through a socio-psychoanalytic lens to explore the manifestation of social dysfunction under the pervasive influence of mass media in postmodern American society. Drawing on Neo-Freudian psychology alongside sociological and media theory, the study argues that Pynchon represents mass media as a dominant ideological force that fragment’s identity, interrupts authentic communication, and raises psychological detachment. The analysis focuses on Oedipal Maas as an embodiment of the postmodern subject, whose increasing alienation, paranoia, and existential disorientation reflect the broader collapse of meaning in late capitalist culture. Surrounded by multiple modes of mediated communication— television, advertising, popular culture, and underground networks— Oedipal repeatedly fails to establish a genuine human connection, revealing the paradox of a society saturated with information yet devoid of understanding. Moving beyond satire, Pynchon’s portrayal of media exposes its role as a substitute for community, spirituality, and selfhood. Ultimately, the paper contends that The Crying of Lot 49 offers a prescient critique of media-driven hyperreality and its corrosive effects on both individual psychology and social cohesion.
Keywords: Social Dysfunction; Mass Media; Postmodernism; NeoFreudianism; Hyperreality Alienation